Pioglitazone Inhibits Diabetes-Induced Atrial Mitochondrial Oxidative Stress and Improves Mitochondrial Biogenesis, Dynamics, and Function Through the PPAR-γ/PGC-1α Signaling Pathway - Zhang, Zhiwei; Zhang, Xiaowei; Meng, Lei; Gong, Mengqi; Li, Jian; Shi, Wen; Qiu, Jiuchun; Yang, Yajuan; Zhao, Jianping; Suo, Ya; Liang, Xue; Wang, Xinghua; et al. (Frontiers in Pharmacology, 2021)
Background: Oxidative stress contributes to adverse atrial remodeling in diabetes mellitus. This remodeling can be prevented by the PPAR-γ agonist pioglitazone via its anti-oxidant and anti-inflammatory effects. In this study, we examined the molecular mechanisms underlying the protective effects of pioglitazone on atrial remodeling in a rabbit model of diabetes. Methods: Rabbits were randomly divided into control, diabetic, and pioglitazone-treated diabetic groups. Echocardiographic, hemodynamic, and electrophysiological parameters were measured. Serum PPAR-γ levels, serum and tissue oxidative stress and inflammatory markers, mitochondrial morphology, reactive oxygen species (ROS) production rate, respiratory function, and mitochondrial membrane potential (MMP) levels were measured. Protein expression of the pro-fibrotic marker TGF-β1, the PPAR-γ coactivator-1α (PGC-1α), and the mitochondrial proteins (biogenesis, fusion, fission-related proteins) were measured. HL-1 cells were transfected with PGC-1α small interfering RNA (siRNA) to determine the underlying mechanisms of pioglitazone improvement of mitochondrial function under oxidative stress. Results: Compared with the controls, the diabetic group demonstrated larger left atrial diameter and fibrosis area, which were associated with a higher incidence of inducible atrial fibrillation (AF). Lower serum PPAR-γ level was associated with lower PGC-1α and higher NF-κB and TGF-β1 expression. Lower mitochondrial biogenesis (PGC-1α, NRF1, TFAM), fusion (Opa1 and Mfn1), and fission (Drp1)-related proteins were detected. Mitochondrial swelling, higher mitochondrial ROS, lower respiratory control rate, and lower MMP were observed. The pioglitazone group showed a reversal of structural remodeling and a lower incidence of inducible AF, which were associated with higher PPAR-γ and PGC-1α. The pioglitazone group had lower NF-κB and TGF-β1 expression levels, whereas biogenesis, fusion and fission-related protein expression was higher. Further, mitochondrial structure and function were improved. In HL-1 cells, PGC-1α siRNA transfection blunted the effect of pioglitazone on Mn-SOD protein expression and MMP collapse in H2O2-treated cells. Conclusions: Diabetes mellitus induces adverse atrial structural, electrophysiological remodeling, and mitochondrial damage and dysfunction. Pioglitazone prevented these abnormalities through the PPAR-γ/PGC-1α pathway.